Interactive first aid guidebook/ Lai Pen San - Lai, Pen San (2001)
'Interactive First Aid Guidebook' is an information-based web sites that will be providing a comprehensive collection of multiple type of first aid situation and solution. The development of these web sites is to increase the awareness of First-Aid knowledge through Internet. Besides that, the development of this interactive-web based web site is to aid and ease the process of learning first aid. From the review of literature have enriched the understanding of Interactivity. 'interactive First aid Guidebook' will be a interactive web site in order to respond dynamically to user control by implementing the computer-aided instruction approach. The Computer-Aided instruction i one of the interactive teaching tools. Database is an important element in developing a web page. Selecting the most suitable database and web server needs a comprehensive research and review from many database approaches. The Study of many types of searching methods before implementing the combination of traditional and new searching methods for the first aid web site's search engine. A survey was conducted to support the type of information that is essential and suitable to be included as part of the web sites module. Besides including an information-based module there will be multimedia based tutorial and a multilevel interactive test conceive of 3 categories; Beginner, Intermediate and Expert. An analysis is required to identify the hardware platform for the web page development, hardware and software requirements, web server and database. During projects analysis, there will be an evaluation on the advantages and disadvantage of web server, database and the programming langauge. Methodolgy selection is an important process for the development process and the types of development approach that will be implementing in the project will be the evolutionary development. Before determine the methodology, a study of the drawbacks of this approach have been done in order to eliminate the unforeseen problems that will occur during the development process. Designing user-friendly interfaces are important; hence improper designed user interactive will lead to a high level of user error. This project interface designs is a t initial stage and will be under modification during the development process. The major functionality that will be included in the project are learn module consist of basic and emergencies first aid, tutorial module, test module and search module. All the modules in "Interactive first Aid Guidebook' will be integrated with text, graphics, animation and multimedia to aid learning process.